South American bot fly types (Diptera: Oestridae) in the Museu de Zoologia da Universidade de São Paulo, Brazil - Letana, Socrates D.; Pape, Thomas; Lamas, Carlos José Einicker (Zootaxa, 2025)
The Museu de Zoologia da Universidade de São Paulo (MZUSP) is one of the most important holdings for Diptera in Latin America, particularly for name-bearing types of the family Oestridae. Ten South American cuterebrine holotypes, a paratype (‘allotype’) of Guerinioestrus bonaerensis Del Ponte, and a paratype of Cuterebrella sabroskyi Guimarães were examined. Specimens with extraneous parts were reevaluated for the holotype of Oricuterebra townsendi Fonseca, and for the non-type female of Guerinioestrus vianai Del Ponte, which is a synonym of Cuterebra grandis (Guérin-Méneville). Type materials that were originally deposited from other natural history museums were discovered and are set for transfer return.